2019
DOI: 10.1109/tvt.2018.2880789
|View full text |Cite
|
Sign up to set email alerts
|

A Game-Theoretic Approach for Fair Coexistence Between LTE-U and Wi-Fi Systems

Abstract: LTE over unlicensed band (LTE-U) has emerged as an effective technique to overcome the challenge of spectrum scarcity. Using LTE-U along with advanced techniques such as carrier aggregation, one can boost the performance of existing cellular networks. However, if not properly managed, the use of LTE-U can potentially degrade the performance of co-existing Wi-Fi access points, which operate over the unlicensed frequency bands. Moreover, most of the existing works consider single operator in their proposals. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…Increasingly, small-cell LTE cellular systems are being planned for deployment in this band. This gives rise to coexistence problems between the cellular (LTE) and Wi-Fi systems which use very different medium access control (MAC) protocols [1], [2]. LTE uses a TDMA/FDMA scheduled approach and Wi-Fi uses a carrier sense multiple access with collision avoidance (CSMA/CA) approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, small-cell LTE cellular systems are being planned for deployment in this band. This gives rise to coexistence problems between the cellular (LTE) and Wi-Fi systems which use very different medium access control (MAC) protocols [1], [2]. LTE uses a TDMA/FDMA scheduled approach and Wi-Fi uses a carrier sense multiple access with collision avoidance (CSMA/CA) approach.…”
Section: Introductionmentioning
confidence: 99%
“…Most existing work on duty cycle based LTE/Wi-Fi coexistence [1], [2], [14], [15] explores issues via analytical and simulation results. While useful, these approaches necessarily ignore several real-time operational challenges that are observed in test-bed deployments.…”
Section: Introductionmentioning
confidence: 99%
“…The results in [22] indicated that the coverage probability of a user increases with the number of accessible UCs. The fairness between the LTE-U and WiFi networks with multiple UCs was also analysed based on game theory in [23], and the fairness among UEs was analysed in a LTE-U driven multi-UC vehicle-to-everything and fullduplex assisted scenarios in [24] and [25], respectively.…”
Section: A Related Work and Motivationmentioning
confidence: 99%
“…The Wardrop equilibrium conditions suggests the delivered price is 0 in such a condition, which leads to 0 profit for the incumbent SP. Then, from the definition of social welfare, we have lim Proof: In Appendix G, we give the equilibrium price and customer mass served by the incumbent and entrant SPs in (23). In this proof, we can still use those results.…”
Section: Appendix F Proof Of Theorem 44mentioning
confidence: 99%